(untitled) (Bangladesh Journal of Zoology, 2015)
Effect of various concentrations of coffee, Coffea arabica, viz. 12.50%, 25% and 50% on the growth and development of the red flour beetle, Tribolium castaneum (Herbst) was determined. Coffee lengthened the larval and pupal periods significantly. There was also a significant reduction in the pupal recovery and adult emergence of the beetle following treatment. The food with 50% coffee had the most detrimental effects on the beetle. Coffee extract could be used as useful botanical pesticide for controlling red flour beetle. Bangladesh J. Zool. 42(2): 211-216, 2014